Postoperative urinary retention: A controlled trial of fixed-dose spinal anesthesia using bupivacaine versus ropivacaine - Shahla Haleem; Ahmad Ozair; Abhishek Singh; Muazzam Hasan; Manazir Athar (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Following spinal anesthesia (SA), patient discharge is often delayed due to postoperative urinary retention (POUR), the incidence of which varies widely. The present study of bupivacaine versus ropivacaine in equianalgesic doses was taken to explore the correlation between time to void urine and time for complete functional recovery. Material and Methods: In this double-blinded study fifty adult patients were assigned to two groups (bupivacaine/ropivacaine) according to alternate case allocation for receiving SA for lower abdominal, perineal, and lower limb surgeries, lasting less than 2 h. Statistical analysis was conducted using an intention-to-treat approach, using Mann-Whitney test for nonparametric data. Primary outcome data could not be obtained for 14 out of the 50 patients due to perioperative bladder catheterization. No patients were lost to follow-up. Results: Both the bupivacaine and ropivacaine groups were comparable in terms of ability to void (8.0 ± 2.3 vs. 7.0 ± 1.2 h;P > 0.05), modified Bromage scale after 4 h of SA (1.8 ± 1.3 vs. 2.6 ± 0.9 grade;P > 0.05), time to complete ambulation (6.7 ± 1.4 vs. 6.1 ± 1.0 h;P > 0.05), and time to negative Romberg test (6.1 ± 1.4 vs. 5.6 ± 0.9 h;P > 0.05), respectively. Strong positive correlations (r = 0.7-0.9) were found between time to void urine and time for complete ambulation. Conclusions: Time to void urine and recovery of motor functions were found comparable statistically when bupivacaine and ropivacaine were used in the doses of 12.5 and 18.75 mg, respectively, for SA. However, group ropivacaine required lesser time to void and no patient developed POUR. Time to void urine was more than the time for ambulation. This may indicate a need for "selective spinal anesthesia" or adjuvant combination technique to accelerate the resolution of a block for ambulatory surgery.